EMPIRICAL STUDY: THE ASSESSMENT OF FINANCIAL STATEMENTS IN INDONESIA ISLAMIC BANK BASED ON IFRS AND AAOIFI STANDARD - Fauzatul Laily Nisa; Lilik Rahmawati (State Islamic Institute (IAIN) Tulungagung, 2022)
Abstract: This study aims to measure how far Indonesian Islamic banking adopts AAOIFI and IFRS standards in its financial reporting. This study uses the annual report of Indonesian Islamic banks in the period 2014-2018 obtained from 5 Islamic banks in Indonesia compiled from the official website of the five banks that were sampled. This research uses a quantitative approach by using a Content Analysis method. This study's results indicate that Indonesian Islamic banking is more inclined to adopt IFRS standards in its annual financial reports (annual report). It can be proven by the large number of percentages of Islamic banking that predominantly meet the total items selected as IFRS standards in its financial statements, compared to the percentage Islamic banking that matches the total items selected as AAOIFI standards. Keywords: financial statements; Islamic banks; IFRS; AAOIFI